Echnatons ,,Monotheismus" - Rezeptionen Amarnas in den Wissenschaften - Koch, Anne (Amarna, 2008)
Positions on Akhenaton in the history of humanities are the topic of this contribution that analyses patterns of constructing Akhenaton mainly as prehistory of Christian monotheism. Egyptologists like H. Brugsch, A. Erman, S. Morenz, J. Assmann, phenomenologists of religion as G. van der Leeuw, F. Heiler and finally Sigmund Freud are part of this adaptation history. It can be seen also as part of the concept of a “European history of religion” (Burkhard Gladigow) that includes also science as productive force of normativity, world views and ideology.